Learning your way in a city: experience and gender differences in configurational knowledge of one’s environment - De Goede, Maartje; Postma, Albert (Frontiers in Psychology, 2015)
Males tend to outperform females in their knowledge of relative and absolute distances in spatial layouts and environments. It is unclear yet in how far these differences are innate or develop through life. The aim of the present study was to investigate whether gender differences in configurational knowledge for a natural environment might be modulated by experience. In order to examine this possibility, distance as well as directional knowledge of the city of Utrecht in the Netherlands was assessed in male and female inhabitants who had different levels of familiarity with this city. Experience affected the ability to solve difficult distance knowledge problems, but only for females. While the quality of the spatial representation of metric distances improved with more experience, this effect was not different for males and females. In contrast directional configurational measures did show a main gender effect but no experience modulation. In general, it seems that we obtain different configurational aspects according to different experiential time schemes. Moreover, the results suggest that experience may be a modulating factor in the occurrence of gender differences in configurational knowledge, though this seems dependent on the type of measurement. It is discussed in how far proficiency in mental rotation ability and spatial working memory accounts for these differences.